Compatibility of common drugs with acetate‐containing balanced electrolyte solutions in pediatric anesthesia. Issue 6 (24th March 2016) - Heiderich, Sebastian; Jürgens, Jonas; Rudolf, Daniel; Dennhardt, Nils; Echtermeyer, Frank; Leffler, Andreas; Sümpelmann, Robert; Lichtinghagen, Ralf; Witt, Lars
Summary: Background: Acetate‐containing balanced electrolyte solutions are frequently used for fluid therapy in pediatric anesthesia, but no studies investigating the compatibility with common anesthetic drugs are available. Aim: To reveal possible incompatibilities between common anesthetic drugs and the acetate‐containing balanced electrolyte solutions BS (Sterofundin ISO; B.Braun Melsungen AG, Melsungen, Germany) and BS‐G1 (E148G1 Päd; Serumwerk Bernburg AG, Bernburg, Germany), with normal saline (NS) as control. Methods: All tested infusion solutions were mixed 1 : 1 with 28 common anesthetic drugs in concentrations used in daily clinical practice. Electrical conductivity, pH, and turbidimetric light diffusion at 405 nm were measured. Macroscopic changes such as gross precipitation, change in color, or bubble formation were also assessed. All measurements were performed immediately after mixing as well as 30 and 60 min after. Results: The vast majority of drugs showed no significant change in pH, electric conductivity, turbidimetric detectable light diffusion, or macroscopic appearance after mixing with BS, BS‐G1, and NS. Phenytoin immediately precipitated in response to all tested solutions as did diazepam. Thiopental precipitated after mixing with BS only. Conclusions: Most of the tested drugs did not show any signs or evidence of incompatibility reactions. However, phenytoin and diazepam should not be in contact with the three tested solutions, including NS. Thiopental should be used with caution because it can precipitate in solutions with a low pH (e.g., BS). Abstract :